Added fat in diets for pigs in early and late finishing - E C Baudon; N Llanes; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2003)
A total of 416 pigs, with an average initial body weight of 127 lb, was used to determine the effect of adding fat in diets for early and late finishing on growth performance and carcass characteristics. Treatments were: a no added fat control; addition of fat in early finishing (127 to 219 lb body weight); addition of fat in late finishing (219 to 280 lb body weight); and addition of fat throughout finishing (127 to 280 lb body weight). For the first period (127 to 219 lb body weight), ADG and F/G were improved by 5 and 9%, respectively, when fat was added in the diet (P<0.03). For the second period (219 to 280 lb body weight) and overall (127 to 280 lb body weight) ADFI was less for pigs fed fat (P<0.003). Also, overall ADG and F/G were improved with inclusion of fat (P<0.07), with the greatest response from inclusion of fat in both phases. Hot carcass weight and carcass yield were increased with inclusion of fat in the diets (P<0.001), and this effect was more pronounced when fat was added in late finishing vs early finishing (P<0.02). In conclusion, the addition of fat to diets for finishing pigs improved growth performance without decreasing carcass leanness. However, adding fat for only the first or second part of the finishing phase was less effective than adding fat for the entire finishing period.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Fat; Finishing; Carcass; Swine